2020
DOI: 10.1002/adem.201901242
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Volume Fraction Influence on Randomly Distributed Short Fiber Tungsten Fiber‐Reinforced Tungsten Composites

Abstract: For future fusion reactors, tungsten (W) is currently the main candidate for the application as plasma‐facing material due to its several advanced properties. To overcome the brittleness of W, randomly distributed short W fiber‐reinforced W (Wf/W) composites have been developed using field‐assisted sintering technology (FAST). Herein, Wf/W materials with different fiber volume fraction (20–60%) are manufactured by FAST process to study the fiber volume fraction influence on the composite properties. Wf/W with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The weak interface positions would form pre‐damage before the matrix failure under high loading. [ 25,26 ] In contrast, the composite here exhibited rather stable flow stress, indicating the proper coordination between the mechanisms, including frictional fiber pullout, elastic bridging between sintered W f and W p , interface debonding between W f and Cu, as well as the resulted crack deflection, as revealed by the fractography in Figure 2b–d. The complex competition among the abovementioned fracture modes is conducive to improving the stability of the energy dissipation behavior of the composite.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The weak interface positions would form pre‐damage before the matrix failure under high loading. [ 25,26 ] In contrast, the composite here exhibited rather stable flow stress, indicating the proper coordination between the mechanisms, including frictional fiber pullout, elastic bridging between sintered W f and W p , interface debonding between W f and Cu, as well as the resulted crack deflection, as revealed by the fractography in Figure 2b–d. The complex competition among the abovementioned fracture modes is conducive to improving the stability of the energy dissipation behavior of the composite.…”
Section: Resultsmentioning
confidence: 93%
“…Very recently, it was reported that a sudden load drop and a followed load increase happened in the W f -reinforced W composites, [25] indicating the unstable crack propagation and rather low defect tolerance due to the crack bridging by fibers and the gradual interface debonding. It was also pointed out that the strength of the W f -reinforced W composites was dominated by the weak interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[111][112][113][114][115] In the following, a short overview on the basic mechanisms and achievements will be given based on the PM production route initially developed at Forschungszentrum Jülich GmbH. [110,111,[116][117][118][119] Typical samples of CVD and PM W f /W are shown in Figure 10 where usual sizes are in the range of 40 mm  40 mm  5 mm or slightly larger for the CVD route.…”
Section: W Compositesmentioning
confidence: 99%
“…Yttrium is an ideal candidate as the interface material for the W f /W composite due to its several advanced properties: good thermal and chemical stability, high mechanical strength, and hardness. [104,116] Studies to understand the pull-out of fibers include modeling. [130] For the developed PM production of W f /W, the homogenous introduction of powder between the fibers is required for good material properties; therefore, short fibers are used in contrast to, Figure 5.…”
Section: W Compositesmentioning
confidence: 99%